Uncommon biphasic behaviour induced by very high metal ion concentrations in HCl/H 2 O/[P 44414 ]Cl and HCl/H 2 O/PEG-600 systems - Sinoimeri, Eris; Maia Fernandes, Victor; Cognard, Jérôme; Pereira, Jorge Fernando Brandão; Svecova, Lenka; Guillotte, Ismaël; Billard, Isabelle (Physical chemistry chemical physics : PCCP, 2020)
In this work, the important role played by metal ions such as Fe( ii / iii ), Cr( iii ) and Ni( ii ) in the formation and binodal behaviour of aqueous biphasic systems (ABS) composed of HCl and the ionic liquid, [P 44414 ]Cl, or the polymer, PEG-600, is investigated. The concentration of metal ions used in this work exceeds several g L −1 for an industrial foreseen application. Experiments have also been carried out by varying the concentration of metal ions at different temperatures. Fe exhibits a totally different behaviour compared to Ni and Cr. In particular, the binodal curves in the presence of the ionic liquid are far from the classical curves found in the literature, displaying an onion-shape form, while for Ni and Cr, the curves follow the classical trend. When any of the three metal ions is mixed with the polymer and HCl medium, only Fe( iii ) induces a biphasic system. Insights into the chemical driving forces at work are discussed.